Fabrication and Performance of Passive Linear Electric Field Frequency Discriminator Filter for 5G Phase-Modulated Microwave Photonic Links - Charalambous, Georgios (Archīum Ateneo, 2020)
We present the circuit design, fabrication in silicon-on-insulator (SOI) platform, and measurement of a linearized electric field discriminator (FD) filter, called Sin-Sin2. This low complexity FD is intended for advanced 5G phase/frequency-modulated direct-detection (PM/FM-DD) links.